Mass media influence - Jumaniyazova Shahlo Zohid kizi; Saparbaeva Gulandam Masharipovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article deals with the impact and influence of mass media in our lives, its benefits and drawbacks, the effects of violence in the media, and it is about how it will influence public opinion.